Ecological aspects of the development of territorial communities of the Lviv region (Economics and region, 2024)
Lviv region is one of the most dynamic in terms of the development of territorial communities, characterized by significant demographic and geographical diversity. Large urban communities, such as Drohobych, Chervonohrad, and Yavoriv, serve as centers of socio-economic activity and significantly impact regional development. They cover large areas and have a high population density, which creates the prerequisites for effectively implementing large-scale infrastructure projects and improving the quality of life for residents. On the other hand, smaller town and rural communities, such as Skhidnytsia and Zabolottsi, although smaller in size and population, still play an important role in ensuring regional stability and preserving cultural identity. Effective management of these diverse communities requires an integrated approach that considers all aspects of their development: environmental, economic, and social. In this context, the signing and implementation of a memorandum for the creation of a regional waste disposal site is a strategically important step. This initiative demonstrates Lviv region's efforts towards sustainable development and improving ecological infrastructure. Participation in the program “Steps for Specialists: Waste Management” helps bring in international experience and enhances the competencies of local specialists in environmental management, which is crucial for overcoming ecological challenges. The analysis of household waste dynamics in Lviv region from 2020 to 2023 showed certain fluctuations in waste volumes, which may be linked to economic and political changes in the country. The growth of environmental awareness among the population and improved waste management have become important factors in reducing the negative impact on the environment. This indicates positive changes in attitudes towards environmental issues and sustainable development in the region. Due to these efforts, Lviv region is moving towards achieving sustainable development goals, allowing it to not only preserve natural resources but also ensure a quality life for current and future generations.
Keywords: territorial communities; sustainable development concepts; Lviv region; environmental issues; household waste